Diversity and distribution of landscape types in Norway. Issue 2 (15th March 2021) - Simensen, Trond; Erikstad, Lars; Halvorsen, Rune
ABSTRACT: Norwegian landscapes are changing at an increasingly rapid rate and therefore systematically structured information about observable landscape variation is required for knowledge-based management of landscape diversity. The purpose of the article is to present the first version of a complete, area covering, evidence-based, landscape type map of Norway, simultaneously addressing geoecological, bioecological and land use related variations. The type system used for the mapping is supported by systematically structured empirical evidence. The results of the mapping procedure, including the geographical distribution and descriptive statistics (abundance and areal coverage), are presented for each of the nine identified major landscape types identified based on coarse-scale landform variation. Within six inland and coastal major types, a large number of minor landscape types are defined based on the composition of geoecological, bioecological, and land use related landscape properties. The results provide new insights into the geography of Norwegian marine, coastal and inland landscapes. The authors discuss potential errors, uncertainties and limitations of the landscape type maps, and address the potential value of the new tool for research, management and planning purposes. They conclude that the results of the study might contribute to knowledge-based spatial planning and management of the unique landscape diversity of Norway.